The Use of Durian Peel Wastes for Bioethanol Production - Soeprijanto Soeprijanto; Ady Prima A; Irene Fransisca T; M. Ibrahim AH; Inayah Wulandari (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2020)
Durian peel (Durio zibethinus Murr) is one of most agricultural residues that have a percentage of approximately 60-75% and inner durian peel (soft layer) contains 11.78% starch that can be used as raw material for ethanol production. This study aimed to determine the effect of durian peel concentration on bioethanol production and the fermentation time required for bioethanol yield. Bioethanol production was carried out in a batch reactor. Two steps of liquefaction and saccharification were carried out to obtain reducing sugar. In liquefaction, 200 g durian peel flour and α-amylase were mixed with water in an Erlenmeyer 2 litter then was heated at 90°C for 2 hours. In saccharification, this mixture was then heated at 60°C for 4 h. The sugar obtained was then fermented by adding yeast as much as 0.2%; urea 0.5%; KH2PO5 0.5% of the amount of reducing sugar obtained. Bioethanol was obtained by fractionation distillation of the fermentation at 78°C. The results showed that in the saccharification using flour with a concentration of 10, 20, 30, and 40% (w/v) produced reducing sugar of 22.23, 44.25, 55.45, and 84.61 g/l, respectively. Bioethanol in the fermentation process was 1.9, 3.6, 5.2, and 7.3%, respectively. It concluded that maximum bioethanol was obtained approximately 7.3% with the reducing sugar used at 84.615 g/l during 4 d fermentation. The bioethanol content obtained was 95% after fractionation distillation.